Combination of immunostimulants with moxidectin in the treatment of animals experimentally infected with Haemonchus contortus - Portella, Luiza Pires; Fernandes, Fagner D'ambroso; Sangioni, Luís Antônio; Ramos, Fernanda; Rodrigues, Fernando de Souza; Menezes, Fernanda Rezer de; Cezar, Alfredo Skrebsky; Faccin, Tatiane Cargnin; Kommers, Glaucia Denise; Vogel, Fernanda Silveira Flores (Semina: Ciências Agrárias, 2021)
Considering the importance of Haemonchus contortus infection in herds along with parasitic resistance, the goal of this study was to evaluate the influence of the administration of adjuvants alone or in combination with anthelmintics for the treatment of H. contortus, in experimentally infected sheep. Thirty sheep of the Texel breed of both genders, raised in a herd located in the subtropical region of Brazil, were used in this experiment. Experimental infection with H. contortus was performed in sheep, and the infected sheep were then separated into groups for the administration of antiparasitic and immunostimulant drugs. The results obtained from the excretion of eggs per gram of feces and the count of parasites during necropsy affirm that the use of adjuvants in combination with anthelmintics is associated with higher efficacy of treatment, lower rate of reinfection, and retardation in the development of anthelmintic drug resistance by H. contortus. Based on these results, we can conclude that the combination of anthelmintics and immunostimulants may favor potential anthelmintic treatments for H. contortus.